Hypocrisies blown away - Abd Razak, Dzulkifli (2005)
FORMER US Education Secretary William J. Bennett showed his true colours recently when he said on a US radio show: "You could abort every black baby in this country and the crime rate would go down" (Time, Oct 10). He had authored a title called Book of Virtues — A Treasury of Great Moral Stories, and one wonders whether this is part of the values he is advocating. For sure, "all (wo)men are created equal" is one value that is significantly relevant to those who are dealing with education, in particular those highranking officials. After all, education is often regarded as an effective tool to create equality. This makes the remark by the former secretary sound awkward, more so when he was quick to back down by saying that his remark was "impossible, ridiculous and morally reprehensible". So, why even think about it, and loudly at that? Maybe the Katrina and Rita hurricanes can reveal some answers.